Trying to change the rules for responding to arbitration unilaterally: The proposed new framework for investor-state dispute settlement for the EU - Ralph Alexander Lorz (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2013)
A new proposal for an internal regulation sheds some light on the European Commission's approach to future bilateral investment treaties to be concluded with the EU, on which negotiations are already underway. Of particular significance in this context is the Commission's desire to reserve the determination of respondent status in future arbitral proceedings for itself. It shows that the EU might strive to modify established mechanisms of investor-state arbitration to fit its internal needs.
Keywords: 330